Social Media Management and Its Effect on Brand Image; A Research in Businesses Operating in the Marmara Region - Kasap, Mesut (Fırat University, 2021)
The purpose of this research is to determine the effect of social media management and management on brand image. For this purpose, relational scanning model, one of the quantitative research models, was used in the study. The sample of the study consists of 312 people who were selected from the research population by simple random sampling method. Social Media Management and Brand Image scale used in the research was used. Descriptive statistical analysis, Structural Equation Model (SEM) analysis and correlation analysis were used in the study. Bootstrapping analysis was used to determine significance values and effects in the study. As a result of the research, it was revealed that social media management and management, which is the main hypothesis of the research, has a positive effect on the brand image. In addition, it was understood from the results of the research that there is a relationship between the power of problem management in social media, which are the sub-dimensions of social media management and management, social media personnel management, social media policies, management policies of social media platforms, supportive roles in social media management and brand image.

Bu araştırmanın amacı sosyal medya yöneticiliği ve yönetiminin marka imajı üzerine etkisini belirlemektir. Bu amaç doğrultusunda araştırmada nicel araştırma modellerinden ilişkisel tarama modeli kullanılmıştır. Araştırmanın örneklemini, araştırma evreninden basit seçkisiz örnekleme yöntemiyle seçilen 312 kişi oluşturmaktadır. Araştırmada Sosyal Medya Yöneticiliği ve Marka İmajı ölçeği kullanılmıştır. Araştırmada tanımlayıcı istatistik analizleri, Yapısal Eşitlik Modeli (YEM) analizi ve korelasyon analizi kullanılmıştır. Araştırmada anlamlılık değerlerini ve etkileri belirlemek amacıyla bootstrapping analizi kullanılmıştır. Araştırma sonucunda araştırmanın ana hipotezi olan sosyal medya yöneticiliğinin ve yönetiminin marka imajı üzerinde olumlu bir etkisinin olduğu ortaya çıkmıştır. Ayrıca sosyal medya yöneticiliği ve yönetiminin alt boyutları olan sosyal medyada ortaya çıkan sorun yönetiminin gücü, sosyal medya personeli yönetimi, sosyal medya politikaları, işletmenin sosyal medya platformlarının yönetim politikaları, sosyal medya yönetiminde destekleyici roller ile marka imajı arasında bir ilişkinin olduğu araştırma sonuçlarından anlaşılmıştır.
SOSYAL MEDYA YÖNETİCİLİĞİ VE YÖNETİMİNİN MARKA İMAJI ÜZERİNE ETKİSİ; MARMARA BÖLGESİNDE FAALİYET GÖSTEREN İŞLETMELERDE BİR ARAŞTIRMA